2012
DOI: 10.1159/000337751
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Generalized Acanthosis Nigricans with Positive Lupus Erythematosus-Related Autoantibodies and Antimicrosomal Antibody: Autoimmune Acanthosis Nigricans

Abstract: Acanthosis nigricans (AN) is a hyperpigmented keratotic skin lesion known to be associated with malignant disease and endocrinopathy. We report a very rare case of generalized AN with Sjögren’s syndrome- and systemic lupus erythematosus-like features but without type B insulin resistance. Neither internal malignancy nor other endocrinological disorders, including glucose intolerance, were detected during a 10-year clinical course with benign diffuse papillomatosis extending from the mucosa of the larynx to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…One case described an association between diffuse AN and an autoimmunity (Sjogren's syndrome and systemic lupus erythematosus–like features) in which the AN responded to immunosuppressive therapy. 7 The authors speculated that other yet-to-be-identified antibodies (ie, other than insulin receptor antibodies) may cause cutaneous findings similar to those seen in patients with insulin resistance (ie, AN). 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case described an association between diffuse AN and an autoimmunity (Sjogren's syndrome and systemic lupus erythematosus–like features) in which the AN responded to immunosuppressive therapy. 7 The authors speculated that other yet-to-be-identified antibodies (ie, other than insulin receptor antibodies) may cause cutaneous findings similar to those seen in patients with insulin resistance (ie, AN). 7 …”
Section: Discussionmentioning
confidence: 99%
“… 7 The authors speculated that other yet-to-be-identified antibodies (ie, other than insulin receptor antibodies) may cause cutaneous findings similar to those seen in patients with insulin resistance (ie, AN). 7 …”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune AN is usually determined by anti-insulin receptor antibodies that appear in autoimmune diseases (e.g., systemic lupus erythematosus) (2022). Cases of AN accompanied by autoimmune manifestations but not type B insulin resistance, which responded to systemic immunosuppressive therapy, have been reported (21,22). It has been speculated that some unknown autoantibodies other than the insulin-receptor antibody might generate mucocutaneous lesions found in AN.…”
Section: Etiologymentioning
confidence: 99%
“…The association of AN with autoimmune disorders like SLE and autoimmune thyroiditis complicated with type B insulin resistance have been reported. [ 6 7 ] A case of generalized AN involving an area from the mucosa of the larynx to the esophagogastric junction, accompanied by autoimmune manifestations but not type B insulin resistance, was described by Kondo et al [ 8 ] The association of scleroderma with AN was described way back in 1966 by Cope et al The patient had profuse blackish villous overgrowth over axillae and inframammary regions along with diffuse systemic sclerosis. [ 9 ] Such association has also been described by Duperrat et al [ 10 ] in 1955 and by Sugawara et al [ 11 ] in 1980.…”
Section: Discussionmentioning
confidence: 99%